Mecanismos de evolução cromossômica e diferenciação cariotípica em espécies das subfamílias Hylinae (tribos Cophomantini e Lophiohylini) e Phyllomedusinae (Hylidae, Anura, Amphibia) - Gruber, Simone Lilian [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
A classe Amphibia, especialmente a família Hylidae, passou por extensas modificações na taxonomia e sistemática, realizadas com base, principalmente, em dados moleculares, mas quase nenhuma contribuição das informações citogenéticas. Os hilídeos são os anuros mais abundantes em número de espécies, porém, a maioria delas foi sequer cariotipada e grande parte das informações disponíveis na literatura está restrita apenas ao número e morfologia dos cromossomos. No presente trabalho, foram cariotipadas 28 espécies da subfamília Hylinae, sendo da tribo Cophomantini Aplastodiscus arildae, A. callipygius, A. eugenioi, A. leucopygius, A. perviridis, Hypsiboas aff. polytaenius, Hypsiboas sp. aff. albopunctatus, H. albomarginatus, H. albopunctatus, H. bakeri, H. caingua, H. caipora, H. crepitans, H. faber, H. latistriatus, H. lundii, H. pardalis, H. polytaenius, H. prasinus, H. raniceps e H. semilineatus; da tribo Lophiohylini, as espécies Aparasphenodon bokermanni, Itapotihyla langsdorffii, Phyllodytes edelmoi, P. luteolus, Trachycephalus sp., T. mesophaeus e T. typhonius; e da subfamília Phyllomedusinae, duas espécies, Phyllomedusa distincta e P. tetraploidea, bem como seus híbridos triploides. A maioria das espécies da subfamília Hylinae compartilha cariótipo 2n=24, FN=48, bandas C majoritariamente centroméricas e RON em cromossomos pequenos do par 11 em Cophomantini e do par 10 em Lophiohylini. As exceções são as do gênero Phyllodytes, da tribo Lophyohylini, cujas espécies têm 2n=22, FN=44 e RON no par 2, e as do gênero Aplastodiscus, da tribo Cophomantini, cujas espécies têm diferentes números cromossômicos de 2n=24, 2n=22, 2n=20 e 2n=18, mas compartilham o mesmo padrão de bandamento C e o mesmo par marcador de RON. As bandas de replicação por incorporação de BrdU...

The Amphibia class, especially the family Hylidae, went through extensive changes in taxonomy and systematics, based mainly on molecular data, but with almost no contribution of cytogenetic information. This family is the most speciose among the anurans, however, the great majority of the species was never karyotyped, and most of the cytogenetic information on hylids available in the literature is restricted to the number and morphology of the chromosomes. In the present work we karyotyped 28 representatives of the subfamily Hylinae, belonging to the tribe Cophomantini the species Aplastodiscus arildae, A. callipygius, A. eugenioi, A. leucopygius, A. perviridis, Hypsiboas aff. polytaenius, Hypsiboas sp. aff. albopunctatus, H. albomarginatus, H. albopunctatus, H. bakeri, H. caingua, H. caipora, H. crepitans, H. faber, H. latistriatus, H. lundii, H. pardalis, H. polytaenius, H. prasinus, H. raniceps e H. semilineatus; to the tribe Lophiohylini the species Aparasphenodon bokermanni, Itapotihyla langsdorffii, Phyllodytes edelmoi, P. luteolus, Trachycephalus sp., T. mesophaeus e T. typhonius; and two species of the subfamily Phyllomedusinae, Phyllomedusa distincta and P. tetraploidea, as well as their triploid hybrids. Most species of the subfamily Hylinae share the same karyotype with 2n=24, FN=48, C bands with predominantly centromeric distribution, and NOR located on small chromosomes belonging to the pair 11 in Cophomantini and to the pair 10 in Lophiohylini. The exceptions are the genus Phyllodytes, from the tribe Lophyohylini, whose species have 2n=22, FN=44 and NOR in the pair 2, and the genus Aplastodiscus, from the tribe Cophomantini, whose species have different chromosome numbers of 2n=24, 2n=22, 2n=20, Abstract and 2n=18, but sharing the same C-banding pattern and the same pair of NOR marker... (Complete abstract click electronic access below)
Keywords: Anura; Anuro; Citogenética animal; Cromossomos; Hibridização in situ; Anfíbio